ERA5 reanalysis for the data interpretation on polarization laser sensing of high-level clouds - Kuchinskaya, Olesya I.; Bryukhanov, Ilia D.; Penzin, Maxim S.; Ni, Evgenii V.; Doroshkevich, Anton A.; Kostyukhin, Vadim V.; Samokhvalov, Ignatii V. 1943-; Pustovalov, Konstantin N.; Bordulev, Iurii S.; Bryukhanova, Valentina V.; Stykon, Alexander P.; Kirillov, Nikolay; et al. (Remote sensing)
Interpreting the results of a high-level clouds (HLCs) lidar study requires a comparison with the vertical proﬁles of meteorological quantities. There are no regular radiosonde measurements of vertical proﬁles of meteorological quantities in Tomsk. The nearest aerological stations are several hundred kilometers away from the lidar and perform radiosonde measurements only a few times a day, whereas lidar experiments are performed continuously throughout the day. To estimate meteorological conditions at the HLC altitudes, we propose to use the ERA5 reanalysis. Its reliability was tested by comparing with the data from ﬁve aerological stations within a radius of 500 km around Tomsk. A labeled database of the lidar, radiosonde, and ERA5 data (2016–2020) for isobaric levels 1000–50 hPa was created. The temperature reconstruction error over the entire altitude range was characterized by an RMSE of 0.8–2.8 ◦C, bias of 0–0.9, and Corr ~1. The accuracy of the relative vertical proﬁles (RMSE 25–40%, Bias 10–22%, and Corr <0.7) and speciﬁc humidity (RMSE 0.2–1.2 g/kg, Bias ~0 g/kg, and Corr ~0) at the HLC altitudes were unsatisfying. The ERA5 data on wind direction and speed for the HLC altitudes were promising.